Genetic diversity and adaptation to aluminum toxicity in local upland rice of Kalimantan - Gunawan Gunawan; Trikoesoemaningtyas Trikoesoemaningtyas; Nurul Hidayatun; Joko Prasetiyono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Acidic soils with high aluminum (Al) toxicity are a major constraint to upland rice productivity in many tropical regions, including Kalimantan. Local rice cultivars often possess adaptive traits that can be utilized for breeding tolerant varieties. This study aimed to investigate the genetic diversity of Kalimantan local upland rice cultivars using SSR markers and their adaptation to aluminum toxicity stress. A total of 93 rice accessions obtained from the Agricultural Gene Bank of IAARD were subjected to both genetic diversity and Al stress adaptation analyses. The genetic diversity analysis used 11 SSR markers, while the adaptation study employed a hydroponic method with 45 ppm Al in Yoshida nutrient solution. Root and shoot growth were observed after 21 days of stress treatment. The SSR markers were highly polymorphic, grouping the accessions into four clusters at a 35% similarity level. Most accessions showed tolerance to Al stress based on relative root and shoot growth parameters. Accessions P. Pulut Timai, Padai Cina, Raya, Parai Paliping, and P. Pulut Ayang/Pang were the most adaptive. Root length, shoot length, and shoot fresh weight exhibited moderate heritability. These findings provide valuable insights for breeding Al-tolerant upland rice adapted to acidic soils. Keywords: adaptability; aluminum stress; molecular marker; SSR; upland rice